Materials+ : creative products - Wong, Rainy (Artpower, 2013)
Materials+: Creative Products' focuses on original design ideas. It features wall clocks made from old vinyl records, comic books used as plant pots, vases made from sticks of dynamite, waste baskets constructed from sheets of recycled newspaper, lampshades made from eggshells, ornaments made from matchsticks; the materials used to make many of the products are not typically associated with the product, resulting in exceptionally creative designs. This innovative book offers access to many unique designs and is an excellent source of inspiration